2018
DOI: 10.21608/ejchem.2018.1642.1143
|View full text |Cite
|
Sign up to set email alerts
|

Performance and emissions characteristics of diesel engine running using biodiesel and its blends with kerosene compared to regular diesel

Abstract: I NCREASE of environmental problems and depletion of fossil fuels are the driving forces to promote biodiesel as an alternative fuel in diesel engines. In the present work, biodiesel was prepared by transesterification of waste cooking oil with methanol, its physical and chemical properties were measured and found to be within acceptable limits of standard specifications of regular diesel fuel. Performance and emissions characteristics of a diesel engine running using biodiesel (B100) and its blends with keros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
3
0
5
Order By: Relevance
“…It has been suggested that the optimal percentage is 15% since it resulted in the best engine performance [18] analyzed the role of 10% DEE into diesel-biodiesel-ethanol and dieselbiodiesel-methanol mixtures. Introducing DEE to a diesel-biodiesel-ethanol combination boosted the period of combustion, cylinder pressure, and BSFC while lowering the emissions of NOx and smoke, according to their findings [19]. Lee and Kim [20] reported that introducing DEE to diesel in different ratios has no influence on engine BTE.…”
Section: Introductionmentioning
confidence: 93%
“…It has been suggested that the optimal percentage is 15% since it resulted in the best engine performance [18] analyzed the role of 10% DEE into diesel-biodiesel-ethanol and dieselbiodiesel-methanol mixtures. Introducing DEE to a diesel-biodiesel-ethanol combination boosted the period of combustion, cylinder pressure, and BSFC while lowering the emissions of NOx and smoke, according to their findings [19]. Lee and Kim [20] reported that introducing DEE to diesel in different ratios has no influence on engine BTE.…”
Section: Introductionmentioning
confidence: 93%
“…Zaher et al [18] juga mempelajari hal yang sama yaitu mencampur minyak diesel (D100) dengan minyak tanah dengan persentase 25% (K25) dan 50% (K50) pada kecepatan mesin 1250 rpm dan 900 rp m dengan beban yang berbeda. Hasil yang didapat bahwa konsumsi bahan bakar menjadi lebih rendah untuk campuran 25% dan 50% minyak tanah dibandingkan dengan biodiesel.…”
Section: Analisa Pembakaran DI Mesin Dieselunclassified
“…Gambar 3. Konsumsi bahan bakar terhadap beban untuk berbagai campuran minyak tanah terhadap minyak diesel pada 1250 rpm [18] Gambar 4. Rasio udara-bahan bakar terhadap beban untuk campuran minyak tanah terhadap minyak diesel pada 1250 rpm [18] Selain itu, penggunaan minyak tanah dibandingkan dengan biodiesel telah dianalisa.…”
Section: Analisa Pembakaran DI Mesin Dieselunclassified
See 1 more Smart Citation
“…The fuel requirement for certain industries in the Kingdom of Saudi Arabia is huge, and have a broad fuel specification making the pyrolysis products a perfect fit. The two main applications of the liquid fuel produced from the process are utility companies producing both desalinated water, and electrical power, and cement companies [23][24]. The heavy fuel oil now used in both utilities, and cement companies are becoming in short supply, while the demands continue to increase due to increased need for water, electricity, and housing projects [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%